Control measures in cases of respiratory syncytial vírus infection in premature newborns: A systematic review (Research, Society and Development, 2023)
Objective: To describe the scientific evidence regarding control measures in cases of Respiratory Syncytial Virus (RSV) infection in preterm newborns. Method: This integrative review was conducted in accordance with the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. The guiding research question was developed using the Population Interest Context (PICo) strategy: preterm newborns (P - population), control measures (I - phenomenon of interest), in case of Respiratory Syncytial Virus infection (Co - context).  Subsequently, the Health Sciences Descriptors (DeCS/BIREME) and Medical Subject Headings (MeSH terms) were consulted, according to Chart 1: Respiratory Syncytial Virus Infection; Prematurity; Control measure. Results: Two studies described recurrent wheezing (RS); another study described two consecutive outbreaks of RSV infection in a Neonatal Intensive Care Unit (NICU), each caused by different RSV genotypes. One article presented current evidence on the etiology, risk factors, diagnosis and management of early and late-onset neonatal sepsis, while another study provided information on the management of community-acquired pneumonia (CAP) in children up to five years of age. Conclusion: The studies found that different control measures can be used in cases of RSV infection in hospitals, such as the use of respiratory precautions, isolation by cohort, monitoring the health status of visitors and staff, prophylactic use of Palivizumab and, above all, frequent and correct hand hygiene by everyone.